RNA-Seq Identifies Circulating miR-125a-5p, miR-125b-5p, and miR-143-3p as Potential Biomarkers for Acute Ischemic Stroke. Issue 8 (29th September 2017) - Tiedt, Steffen; Prestel, Matthias; Malik, Rainer; Schieferdecker, Nicola; Duering, Marco; Kautzky, Veronika; Stoycheva, Ivelina; Böck, Julia; Northoff, Bernd H.; Klein, Matthias; Dorn, Franziska; Krohn, Knut; et al.
Abstract : Rationale: : Currently, there are no blood-based biomarkers with clinical utility for acute ischemic stroke (IS). MicroRNAs show promise as disease markers because of their cell type–specific expression patterns and stability in peripheral blood. Objective: : To identify circulating microRNAs associated with acute IS, determine their temporal course up to 90 days post-stroke, and explore their utility as an early diagnostic marker. Methods and Results: : We used RNA sequencing to study expression changes of circulating microRNAs in a discovery sample of 20 patients with IS and 20 matched healthy control subjects. We further applied quantitative real-time polymerase chain reaction in independent samples for validation (40 patients with IS and 40 matched controls), replication (200 patients with IS, 100 healthy control subjects), and in 72 patients with transient ischemic attacks. Sampling of patient plasma was done immediately upon hospital arrival. We identified, validated, and replicated 3 differentially expressed microRNAs, which were upregulated in patients with IS compared with both healthy control subjects (miR-125a-5p [1.8-fold; P =1.5×10 −6 ], miR-125b-5p [2.5-fold; P =5.6×10 −6 ], and miR-143-3p [4.8-fold; P =7.8×10 −9 ]) and patients with transient ischemic attack (miR-125a-5p: P =0.003; miR-125b-5p: P =0.003; miR-143-3p: P =0.005). Longitudinal analysis of expression levels up to 90 days after stroke revealed a normalization to control levels for miR-125b-5p and miR-143-3p starting at day 2 while miR-125a-5p remained elevated. Levels of all 3 microRNAs depended on platelet numbers in a platelet spike-in experiment but were unaffected by chemical hypoxia in Neuro2a cells and in experimental stroke models. In a random forest classification, miR-125a-5p, miR-125b-5p, and miR-143-3p differentiated between healthy control subjects and patients with IS with an area under the curve of 0.90 (sensitivity: 85.6%; specificity: 76.3%), which was superior to multimodal cranial computed tomography obtained for routine diagnostics (sensitivity: 72.5%) and previously reported biomarkers of acute IS (neuron-specific enolase: area under the curve=0.69; interleukin 6: area under the curve=0.82). Conclusions: : A set of circulating microRNAs (miR-125a-5p, miR-125b-5p, and miR-143-3p) associates with acute IS and might have clinical utility as an early diagnostic marker. Abstract : Supplemental Digital Content is available in the text.